Application of biohumate and optimization of alternative energy sources by solar energy for pumping on sloping and rocky land in West Bacukiki District, Parepare City - Iradhatullah Rahim; Jasman Jasman; Nurhaeda Nurhaeda; Fatmawati Fatmawati (Community Empowerment, 2023)
West Bacukiki District is a food source-producing area in Parepare City, South Sulawesi. However, this area is located on rocky hills and has a slope of up to 25°. It was quite difficult for the management of water and soil because the water at a height of discharge is very little. The condition was felt by the Barangan Farmers Group who cultivate shallots. Water has to be pumped and it costs a lot to buy fuel for the pumping machine. One solution that can be done is a pumping system with abundant alternative energy sources and the provision of organic fertilizer products to having nutrient needs. This activity was carried out in 4 stages, namely socialization of activities, optimizing solar panels, repairing water pumps, and bio-humic application. This activity really helps KT Barangan in agricultural cultivation activities by increasing the discharge of pumpable water and increasing the organic matter of rocky and sloping soils on their land.